A Museum Addition for a University: an entry in the James Harrison Steedman Competition - Thomas Lance Braht (Oz, 1981)
Design Situation. During the 1880's in a midwestern city a small church was built at the edge of a college campus. This church was faithfully built in the French Romanesque manner by knowledgeable and well-traveled architects…